Bureaucratic Accountability Analysis Through Application-Based Monitoring System in the Enforcement of Class C Mineral Quarrying in Kupang Regency - Naftali Arkilaus Natumnea (Journal of Political Innovation and Analysis, 2026)
Background: Bureaucratic accountability in the management of Class C mineral quarrying (Galian C) in Kupang Regency faces a serious crisis, evidenced by alleged revenue leakage of IDR 570 million across three budget years (2019–2021) and the persistence of widespread illegal mining activities despite existing regulatory frameworks.Objective: This study aims to analyze bureaucratic accountability in the enforcement of Galian C mining through a digital application-based monitoring system launched in April 2025 by the Kupang Regency Government.Method: This research employs a qualitative descriptive approach relying on secondary data sources, including digital media reports (Timur Today, Victory News, Koran Timor, Lintas NTT), official government documents (Kupang Regency Government website, NTT Provincial ESDM IUP data), and academic publications. Data validation was conducted through source triangulation, requiring each key finding to be confirmed by at least two independent sources.Findings and Implications: The results indicate that the implementation of the Galian C Monitoring Application is still in its early stages, classifiable at Layne and Lee’s first e-government stage (cataloguing), and is hampered by three critical deficiencies: (1) limited ASN human resource capacity and dependence on external STIKOM Uyelindo personnel; (2) underdeveloped digital infrastructure across Kupang Regency’s 5,298.13 km² and 24 sub-districts; and (3) weak inter-agency coordination among Bapenda, Dinas ESDM, Satpol PP, and Polres Kupang.Conclusion: Bureaucratic accountability in Galian C enforcement in Kupang Regency has not yet functioned optimally; its success requires sustained ASN capacity building, reinforced cross-institutional coordination, digital infrastructure improvement, and firm law enforcement mechanisms.